PENGARUH KOMPETENSI SOSIAL GURU TERHADAP INTERAKSI BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 15 KOTA BANJARBARU - Nurainah Nurainah; Imaniah Elfa Rachmah (Program Studi PAI STAI Al Falah Banjarbaru, 2019)
This study is an attempt to find out the influence of social competence of teachers with students learning interactions in the SMP 15 Banjarbaru. Formulation of the problem in this research is how high social competence of teachers, and how high the interaction of student learning in 228 15 Banjarbaru, and what factors affected it. It is aimed at teaching and learning in the process in order to get success, for it is very necessary competence of teachers in social inclusion students in the subjects taught to pay attention resulting in the process of teaching and learning desired. The goal in this research are (1) to find out how the social competence of the teacher against the subjects of Islamic education at SMP 15 Banjarbaru, (2) to find out how the interaction of student learning against the subjects of religious education Islam in 228 15 Banjarbaru, (3) is there any significant influence of social competence among teachers towards interaction students can study subjects of Islamic education at SMP 15 Banjarbaru. The study of quantitative analysis techniques with a statistics product moment. Data collection in the field by using the technique of the now, the population in this research is the most students who are in class IX as much as 15 people from the total to 82 people. Based on the results of research performed can be concluded that there was significant influence between the Social competence of the teacher against Student Learning Interactions in the SMP 15 Banjarbaru well enough, or significant. This can be seen from the test results correlation product moment. With the results of calculation show that xy is greater than rtabel5% (0.514 > 0.686) and greater rtabel1% rxy (0.686 > 0.641) then the hypothesis: there are causal relations Ha due to Social Competence among Teachers Towards students ' Learning Interactions in the SMP 15 City Long Beach received. Key Words: Teacher, Social Competence, Learning Interactions, Islamic Education.